Genomic Analyses Provide Insights Into the Evolutionary History and Genetic Diversity of Auricularia Species - Dai, Yueting; Li, Xiao; Song, Bing; Sun, Lei; Yang, Chentao; Zhang, Xin; Wang, Yanfeng; Zhang, Zhiwu; Fu, Yongping; Li, Yu (Frontiers in Microbiology, 2019)
Species in the genus Auricularia play important roles for people’s food and nutrition especially Auricularia cornea and A. heimuer. To understand their evolutionary history, genome structure, and population-level genetic variation, we performed a high-quality genome sequencing of Auricularia cornea and the coresponding comparative genomic analysis. The genome size of A. cornea was similar to Auricularia subglabra, but 1.5 times larger than that of A. heimuer. Several factors were responsible for genome size variation including gene numbers, repetitive elements, and gene lengths. Phylogenomic analysis revealed that the estimated divergence time between A. heimuer and other Auricularia is ~79.1 million years ago (Mya), while the divergence between A. cornea and A. subglabra occurred in ~54.8 Mya. Population genomic analysis also provided insight into the demographic history of A. cornea and A. heimuer, indicating that their populations fluctuated over time with global climate change during Marine Isotope Stage 5-2. Moreover, despite the highly similar external morphologies of A. cornea and A. heimuer, their genomic properties were remarkably different. The A. cornea genome only shared 14% homologous syntenic blocks with A. heimuer and possessed more genes encoding carbohydrate-active enzymes and secondary metabolite biosynthesis proteins. The cross-taxa transferability rates of simple sequence repeat (SSR) and insertion or deletion (InDel) markers within the genus Auricularia were also lower than that previously observed for species within the same genus. Taken together, these results indicate a high level of genetic differentiation between these two Auricularia species. Consequently, our study provides new insights into the genomic evolution and genetic differentiation of Auricularia species that will facilitate future genetic breeding.